Pengaruh Skeptisme Profesional dan Audit Investigatif terhadap Pengungkapan Fraud - Nanditya Andini; Eva Yanis Lafione; Nera Marinda Machdar (Jurnal Riset Ekonomi dan Akuntansi, 2024)
An important consideration in every scientific article is the author's knowledge of theory and previous research. Previous research can improve phenomena and theories involving correlations between variables. The purpose of writing this article is to develop a hypothesis of the influence between variables to be used in subsequent research. The findings from this literature review are: 1) professional skepticism has a positive and significant effect on fraud disclosure; 2) investigative audits have a positive and significant effect on fraud disclosure.